Comparison of 2D and 3D bone marrow cell growth on alginate hydrogels - Wang, L; Barralet, J; Lawson, M; Triffitt, J; Cooper, P; Shelton, R (2004)
The effect of the various concentrations of MVG alginate hydrogels on the proliferation behavior of rat bone marrow cells (rBMC) was investigated. The rMBC were harvested from the femora of adult Wistar rat and 4 × 14 4 cells were seeded into the different concentration of alginate discs and tubes. The MTT assay was used to determine the cell number. It was observed that higher concentrations of the MVG disc decreased the proliferation rate. The rate of proliferation of rBMC on 3% MVG and modified 3% MVG (collagen I plus TCP) 2D discs were statistically greater than cultures on 8% MVG and modified 8% MVG (collagen I and TCP) discs. It was also found that growth rate of rBMC on 8% alginate tubes was higher than on 8% discs.